Cysteine supplementation enhanced inhibitor tolerance of Zymomonas mobilis for economic lignocellulosic bioethanol production. (April 2022) - Yan, Xiongying; Wang, Xia; Yang, Yongfu; Wang, Zhen; Zhang, Haoyu; Li, Yang; He, Qiaoning; Li, Mian; Yang, Shihui
Graphical abstract: Highlights: Cysteine effectively enhanced cell growth and furfural tolerance in Z. mobilis 8b. Cysteine mediated GSH and H2 S production to reduce ROS induced by furfural. Cysteine enhanced robustness against acetate, ethanol and corncob hydrolysate. Abstract: Inhibitors in lignocellulosic hydrolysates are toxic to Zymomonas mobilis and reduce its bioethanol production. This study revealed cysteine supplementation enhanced furfural tolerance in Z. mobilis with a 2-fold biomass increase. Transcriptomic study illustrated that cysteine biosynthesis pathway was down-regulated while cysteine catabolism was up-regulated with cysteine supplementation. Mutants for genes involved in cysteine metabolism were constructed, and metabolites in cysteine metabolic pathway including methionine, glutathione, NaHS, glutamate, and pyruvate were supplemented into media. Cysteine supplementation boosted glutathione synthesis or H2 S release effectively in Z. mobilis leading to the reduced accumulation of reactive oxygen species (ROS) induced by furfural, while pyruvate and glutamate produced in the H2 S generation pathway promoted cell growth by serving as the carbon or nitrogen source. Finally, cysteine supplementation was confirmed to enhance Z. mobilis tolerance against ethanol, acetate, and corncob hydrolysate with an enhanced ethanol productivity from 0.38 to 0.55 g −1 ∙L −1 ∙h −1 .